Hericium caput-medusae (Bull.:Fr.) Pers. polysaccharide enhance innate immune response, immune-related genes expression and disease resistance against Aeromonas hydrophila in grass carp (Ctenopharyngodon idella). Issue 72 (January 2018) - Gou, Changlong; Wang, Jiazhen; Wang, Yuqiong; Dong, Wenlong; Shan, Xiaofeng; Lou, Yujie; Gao, Yunhang
Abstract: The objective was to add 0, 400, 800 or 1200 mg/kg of Hericium caput-medusae polysaccharide (HCMP) to the basal diet of grass carp ( Ctenopharyngodon idella ) and determine effects on humoral innate immunity, expression of immune-related genes and disease resistance. Adding HCMP enhanced ( P < 0.05) bactericidal activity at 1, 2 and 3 weeks and also lysozyme activity, complement C3, and SOD activity at 2 and 3 weeks. Supplementing 800 or 1200 mg/kg of HCMP for 2 or 3 weeks increased ( P < 0.05) serum concentrations of total protein, albumin and globulin. Two immune-related genes (IL-1β and TNF-α) were up-regulated ( P < 0.05) in HCMP supplemented groups given 800 or 1200 mg/kg HCMP after 2 and 3 weeks of feeding. Expression of anti-inflammatory cytokine IL-10 was down-regulated ( P < 0.05) after receiving 800 or 1200 mg/kg HCMP for 2 or 3 weeks. Fish fed 800 mg/kg HCMP had maximal disease resistance against Aeromonas hydrophila (65.4%). In conclusion, HCMP enhanced immune response and expression of immune-related genes and increased disease resistance against Aeromonas hydrophila in grass carp, with greatest effects in fish given 800 mg/kg HCMP for 3 weeks. Highlights: HCMP provoked the innate immune response of grass carp. HCMP provoked the expression of immune-related genes in grass carp. HCMP enhanced the disease resistance against Aeromonas hydrophila in grass carp. The optimum supplemented dose of HCMP is 800 mg/kg.